Penguatan Ketahanan Pangan dengan Sistem Agroforestri di Kabupaten Tapanuli Selatan : Analisis Faktor-Faktor Ekologi dan Ekonomi - Harahap, Parmanoan (UNIVERSITAS LABUHANBATU, 2025)
Agroforestry is a practice that combines the cultivation of food crops and forests in an integrated system. This method has proven effective in improving food security and environmental sustainability. The aim of this study is to analyze the ecological and economic factors of the community in strengthening food security with an agroforestry system in South Tapanuli Regency. Data collection used a purposive sampling method, based on specific traits and characteristics. Respondents were land managers under forest stands with an agroforestry pattern. The population size was determined using the Slovin formula. The analysis used was descriptive and quantitative. The results showed that agroforestry has an important economic function for the local community. Its primary role is not food production but rather as a source of income and capital. Income from agroforestry generally covers daily needs from the regularly harvested produce. The commodities grown on agroforestry land include corn, cocoa, coffee, snake fruit, oil palm with stands of rubber, sugar palm, and durian. On a land area of two to three hectares, the average yield of corn is 0.9 tons/year, cocoa 1.2 tons/year, coffee 1.08 tons/year, snake fruit 69.6 tons/year, palm oil 11.29 tons/year, palm sugar 0.57 tons/year, rubber 14.64 tons/year, and durian 1,250 fruits/year. Through its ecological function, agroforestry can reduce the rate of surface flow, leaching of soil nutrients and erosion, because the presence of trees prevents these processes from occurring, so that the nutrient content in the soil will be maintained. Keywords: agroforestry, ecology, economics and food security